Faith, Networks, and the Ballot: Unveiling the Hidden Drivers of Voting Intentions in Indonesia's 2024 Election - Setiawan, Tery; AS Hikam, Muhammad; Suhartomo, Antonius (UIN Sunan Gunung Djati Bandung, 2024)
This study investigates the extent to which social network characteristics, religious identity, and past political participation influence voting intentions in Indonesia's 2024 general election, with a particular focus on the implications of religiosity in a predominantly Muslim society. A quantitative survey method was employed, gathering primary data through both online and offline surveys from 314 participants across selected locations in Indonesia. Multilevel modelling techniques were used to analyse the relationship between social network characteristics, religious identity, and voting intentions. The results revealed that social network characteristics, such as the frequency of interaction and socio-political discussions, do not significantly influence voting intentions. In contrast, religiocentrism negatively impacts voting intentions, suggesting that individuals with more conservative religious beliefs are less likely to vote. However, past offline political participation was found to be a strong positive predictor of voting intentions. These findings highlight the need for targeted interventions that address the concerns of conservative religious groups and reinforce the civic duty associated with voting. Understanding the limited role of social networks in this context can inform strategies to increase voter turnout in future elections. This study provides new insights into the complex interplay between religious identity, social networks, and political behaviour in Indonesia, a predominantly Muslim and culturally diverse nation, particularly in the post-pandemic socio-political landscape.